Evolution of the Sauropterygian Labyrinth with Increasingly Pelagic Lifestyles - Neenan, James M; Reich, Tobias; Evers, Serjoscha W; Druckenmiller, Patrick S; Voeten, Dennis F A E; Choiniere, Jonah N; Barrett, Paul M; Pierce, Stephanie E; Benson, Roger B J (Current biology, 2017)
Sauropterygia, a successful clade of marine reptiles abundant in aquatic ecosystems of the Mesozoic, inhabited nearshore to pelagic habitats over >180 million years of evolutionary history [1]. Aquatic vertebrates experience strong buoyancy forces that allow movement in a three-dimensional environment, resulting in structural convergences such as flippers and fish-like bauplans [2, 3], as well as convergences in the sensory systems. We used computed tomographic scans of 19 sauropterygian species to determine how the transition to pelagic lifestyles influenced the evolution of the endosseous labyrinth, which houses the vestibular sensory organ of balance and orientation [4]. Semicircular canal geometries underwent distinct changes during the transition from nearshore Triassic sauropterygians to the later, pelagic plesiosaurs. Triassic sauropterygians have dorsoventrally compact, anteroposteriorly elongate labyrinths, resembling those of crocodylians. In contrast, plesiosaurs have compact, bulbous labyrinths, sharing some features with those of sea turtles. Differences in relative labyrinth size among sauropterygians correspond to locomotory differences: bottom-walking [5, 6] placodonts have proportionally larger labyrinths than actively swimming taxa (i.e., all other sauropterygians). Furthermore, independent evolutionary origins of short-necked, large-headed "pliosauromorph" body proportions among plesiosaurs coincide with reductions of labyrinth size, paralleling the evolutionary history of cetaceans [7]. Sauropterygian labyrinth evolution is therefore correlated closely with both locomotory style and body proportions, and these changes are consistent with isolated observations made previously in other marine tetrapods. Our study presents the first virtual reconstructions of plesiosaur endosseous labyrinths and the first large-scale, quantitative study detailing the effects of increasingly aquatic lifestyles on labyrinth morphology among marine reptiles.
Keywords: ekosystém; plazi; Tomography, X-Ray Computed; zkameněliny; Reptiles; plavání; počítačová rentgenová tomografie; Animals; Fossils; biologická evoluce; Swimming; vnitřní ucho; Ear, Inner; Biological Evolution; Ecosystem; zvířata